Engine overspeed protection and control method - GOU ZHIYONG; SHANG HAIKUN; SHEN JIE; WANG YANBING; XU MINGSHENG; DONG CHANGLONG; HE JIANFENG (2012)
The invention discloses an engine overspeed protection and control method, which is based on an engine overspeed protection and control system and particularly comprises the following steps: A, detecting the working condition of a fuel cut electromagnetic valve; B, detecting the engine speed by a speed sensor; C, automatically starting protection in case of overspeed; D, starting power-off protection for the engine; E, detecting the working condition of the speed sensor; and F, manually detecting whether or not the system is normal. The engine overspeed protection and control method can randomly detect all inactive elements in the system during the normal operation of the engine, so that failure in circuits and elements of the system can be detected timely; when the failure occurs, an alarm can be issued timely and displayed to the operator, so as to remind the operator of timely maintenance; therefore, the safety performance of the engine is greatly improved, and the personal safety of the user can be effici